Monocular Elevation Deficiency: A Case Series of Surgical Outcome - Mohammad Reza Talebnejad; Gholam Abbas Roustaei; Mohammad Reza Khalili (Iranian Journal of Medical Sciences, 2014)
Background: Inferior rectus recession, Knapp procedure, partial tendon transposition, and combined procedure are different surgical procedures in the management of monocular elevation deficiency (MED). Only a few studies have been published on the management of this problem. In this study, we report our experience with patients with MED focusing on the indications and types of surgery in the south of Iran. Methods: In this case series, a computerized database review on 4773 patients with strabismus was performed and 18 patients diagnosed as having MED who had undergone strabismus surgery were enrolled. Results: Of the 18 patients, 13 had only hypotropia and 5 had horizontal deviation as well. Preoperative vertical deviation was between 15 and 60 prism diopter (mean±SD=25.8±10.7 PD). Fourteen patients had positive forced duction test on elevation. Seventeen patients had ptosis twelve of them had true ptosis and the remaining 5 had pseudoptosis). The mean postoperative follow-up was 24.4 months. Four patients underwent Knapp procedure, 12 patients underwent inferior rectus recession, and for 2 patients a combined procedure was performed. The mean postoperative hypotropia was 6.1±7.9 PD. Twelve out of the 18 patients were corrected to within five PD of orthophoria and no one was found with overcorrection. Conclusion: Although MED is etiologically multifactorial, satisfactory surgical results can be achieved by judicious selection of the surgical technique based on the results of the forced duction test.